Unleashed - Leterrier, Louis, 1973-; Li, Jet, 1963-; Freeman, Morgan; Hoskins, Bob.; Condon, Kerry, 1983-; Regan, Vincent, 1966-; Morel, Pierre; Massive Attack (Musical group); Universal Pictures (Firm) (Universal City, CA : Universal, 2005)
This is the story of Danny, a slave who has lived his whole life without any sort of normal human interaction, with the mind and personality of a young child, Danny has only ever learned one lession in life: how to fight.
Cinematographer, Pierre Morel ; editor, Nicolas Trembasiewicz ; music, Massive Attack ; costume designer, Olivier Beriot ; production designer, Jacques Bufnoir ; martial arts choreographer, Yuen Wo Ping.
Jet Li, Morgan Freeman, Bob Hoskins, Kerry Condon, Vincent Regan, Dylan Brown, Tamer Hassan, Michael Jenn.
MPAA rating: Unrated.
DVD, region 1, widescreen (2.35:1) presentation; Dolby Digital 5.1 surround, DTS 5.1 surround, dual layer, single sided.
English dialogue, English, French or Spanish subtitles; closed-captioned.
Keywords: Hand-to-hand fighting -- Drama; Slaves -- Drama; Piano technicians -- Drama; Mentoring -- Drama; Combate mano a mano -- Teatro; v; Feature films; Films for the hearing impaired; Martial arts -- Feature; Crime -- Feature